Epidemiological investigation of the first 5685 cases of SARS-CoV-2 infection in Qatar, 28 February–18 April 2020. Issue 10 (7th October 2020) - Al Kuwari, Hanan M; Abdul Rahim, Hanan F; Abu-Raddad, Laith J; Abou-Samra, Abdul-Badi; Al Kanaani, Zaina; Al Khal, Abdullatif; Al Kuwari, Einas; Al Marri, Salih; Al Masalmani, Muna; Al Romaihi, Hamad E; Al Thani, Mohamed H; Coyle, Peter V; et al.
Abstract : Objective: To define the epidemiological curve of COVID-19 in Qatar and determine factors associated with severe or critical illness. Design: Case series of first 5685 COVID-19 cases in Qatar. Setting and participants: All confirmed COVID-19 cases in the State of Qatar between 28 February and 18 April 2020. Main outcome measures: Number of total and daily new COVID-19 infections; demographic characteristics and comorbidity burden and severity of infection; factors associated with severe or critical illness. Results: Between 28 February and 18 April 2020, 5685 cases of COVID-19 were identified. Median age was 34 (IQR 28–43) years, 88.9% were male and 8.7% were Qatari nationals. Overall, 83.6% had no concomitant comorbidity, and 3.0% had three or more comorbidities. The overwhelming majority (90.9%) were asymptomatic or with minimal symptoms, with 2.0% having severe or critical illness. Seven deaths were observed during the time interval studied. Presence of hypertension or diabetes was associated with a higher risk of severe or critical illness, but age was not. The epidemiological curve indicated two distinct patterns of infection, a larger cluster among expatriate craft and manual workers and a smaller one among Qatari nationals returning from abroad during the epidemic. Conclusion: COVID-19 infections in Qatar started in two distinct clusters, but then became more widespread in the population through community transmission. Infections were mostly asymptomatic or with minimal symptoms and associated with very low mortality. Severe/critical illness was associated with presence of hypertension or diabetes but not with increasing age.